Serbarea de la Putna – un eveniment incomod la graniţa imperiului austro-ungar - Valentin Coşereanu (Revista de Istorie și Teorie Literară)
Breaking a part of a country – no matter how small and large –, that piece, wherever you put it, will keep its inner nature, the substance and the specific lifeblood of the people you broke it from, until it will fiind an opportunity to reunify the identity of its nation, as soon as the historical circumstances appear favorable for it. In Habsburg Bukovina the celebration at Putna was the half-fulfilled cause of such opportunity, and Eminescu, the soul of event.